Infection of Animals with the Influenza Virus After a Preliminary Administration of the Preparation â€œCryocell-Haemocordâ€. Report II. Investigation of Morpho-Functional State of Murine Immunocompetent Organs - Volina, V. V.; Brovko, Ye. V.; Onasenko, Ye. S.; Ponomareva, V. L. (Problems of Cryobiology and Cryomedicine, 2010)
The influence of a preliminary administration of the preparation â€œCryocell-Haemocordâ€ on morpho-functional state of lungs, thymus, lymph nodes and spleen of animals infected with a lethal dose of the influenza virus A/Victoria was studied. The data obtained attest to an anti-virus activity of the preparation â€œCryocell-Haemocordâ€, which manifested itself as absence of dystrophic and necrotic injuries, maintenance of cell structures in organs of immune protection and lungs of animals infected with the influenza virus.